Performance evaluation of packet reordering on concurrent multipath transmissions for transport virtualisation. (8th April 2011) - Zinner, Thomas; Tran-Gia, Phuoc; Tutschku, Kurt; Nakao, Akihiro
From the viewpoint of communication networks virtualisation (NV) extends beyond pure operational issues and addresses many impasses of the current Internet. The idea of transport virtualisation (TV) progresses the capabilities of NV and enables the independence from a specific network transport resource. The independence is achieved by pooling multiple transport resources and selecting the best resources for exclusive or concurrent use. However, the application and selection of concurrent paths is rather complex and introduces inevitable packet reordering due to different stochastic delay characteristics on the used paths. Packets arriving at the destination out-of-order have to be stored in a resequencing buffer before reassembled packets are forwarded to the application. We provide a simulation framework based on discrete event simulation which allows an evaluation of the resequencing buffer occupancy. Further, we perform an analysis of the fundamental behaviours and factors for packet reordering in concurrent multipath transmissions.